Influential factors of Islamic insurance adoption: an extension of theory of planned behavior. Issue 6 (8th October 2019) - Raza, Syed Ali; Ahmed, Rehan; Ali, Muhammad; Qureshi, Muhammad Asif
Abstract : Purpose: The role of insurance is a backbone for consumers to secure their future. It is important to know where to invest and what are the benefits. Therefore, for the Muslim segment, Islamic insurance system provides Riba (interest)-free environment where consumers invest their money and recover their losses according to sharia. This paper aims to examine the determinants that influence purchase intention of consumers toward Islamic insurance (Takaful) adoption in Pakistan with the help of the modified theory of planned behavior (TPB). Design/methodology/approach: The authors added four specific variables related to Islamic sharia compliance in the conventional form of the TPB. The relationship among the variables is assessed by using partial least squares structural equation modeling, while the data are collected from 305 respondents. Findings: The results suggest that attitude, subjective norm and perceived behavioral control are strong predictors of an Islamic insurance adoption in Pakistan. Moreover, factors such as compatibility, relative advantage and awareness have positive and significant impacts on takaful participation. A negative but insignificant relation is found between perceived risk and intention. Practical implications: This paper provides insight for understanding the factors that lead to consumers' purchase intention of Islamic insurance. Originality/value: This paper makes a unique contribution to the literature with reference to Pakistan, being a pioneering attempt to investigate the factors of Islamic insurance adoption by modifying the TPB and applying more rigorous statistical techniques like confirmatory factor analysis (CFA) and partial least square structural equation modeling.